Terreiro de umbanda em Aracaju : análise das relações interpessoais conflitivas - Nunes, Renata Rennó (2016)
The work aims to analyze the life story of the leader of a ¨terreiro de Umbanda¨, keeping in my that interpersonal relationships are what keep the group together. His story is intertwined with the history of the ¨terreiro¨, and after his experiences with other religions, I seek to understand how he organizes the ¨terreiro¨ and its influences, and from recorded interviews, understand how (and if) conflicts happen and how they interfere with rituals . In the field work, I made use of filming, recording and informal conversations, beside my observation in the ¨terreiro¨. With the collected data, I analyze through the concepts of conflict, power and liminality how the relations happens in the ¨terreiro¨, and especially how the leader sees the conflicts and how he interact with different groups. This work had two stages: my first insertion in the terreiro, from April to September 2014 and from March to October 2015. This gap of time was important for the literature to relate with my experiences. Although I could not always interview all the participants I wanted, the interviews gave me subsidy for me to realize that the group remains tight, despite the conflicts, and that Fabio does not clearly define the groups, which seems to trigger more conflicts. The study of Fabio's life story showed how his life and the formation of the terreiro are mixed, and bring new elements to the Umbanda, as Jurema and the Daime. Umbanda, as a religion based on orality, makes that every yard has its particular rules, but Fabio brings new elements to the religion in a particular way, adding a bit of each religions through which he passed in Umbanda.